The delineation of ecological redline area for catchment sustainable management from the perspective of ecosystem services and social needs: A case study of the Xiangjiang watershed, China - Dengshuai Chen (Elsevier, 2021)
China’s river basin ecosystems are facing serious environmental and structural fragmentation problems. However, there are no complete ecological redlines specifically for watershed ecological conservation. This study considers the Xiangjiang River Basin (XJRB) to propose a framework delineating the ecological redline area (ERA) on a watershed scale and highlights policy recommendations. It combines several evaluating indicators for coupling the response mechanism between human demand and ecological protection. Overall, the water supply in the XJRB meets the social demand. However, water supply in some places, such as the core area of Changsha Zhuzhou Xiangtan Urban Agglomeration and the Hengyang urban area, is still insufficient. This study considers ecosystem service functions, ecological sensitivities, and social needs and estimates the ERA of the XJRB to be 36,057 km2, accounting for 38% of the total watershed. The key ecological functional areas account for 60% of the total redline area and are concentrated in the upper reaches. Compared with the current method conducted at the national and administrative level, the redline area defined in this study by the sub-basin scale exhibits better connectivity and integrity. Moreover, the study can help ensure an accurate placement of the ecological redline while also providing an important reference for redline delineation of other river basins.